Long distance run induced hydration and kidney function changes in marathoners - Luiz Guilherme Cruz Gonçalves; Rodrigo Leal de Queiroz Thomaz de Aquino; Enrico Fuini Puggina (Universidade Estadual Paulista (UNESP), 2015)
AbstractThe aim of the study was to verify the hydration status and the kidney function in marathoners during the training season and after a marathon race. Nine male runners were investigated during 12 weeks of training. Urine was collected in four moments; in the beginning (C1) and during (C2) the training program, before (C3) and after (C4) the competition. Urine pH was measured using reagent tapes, urine density with a refractometer, protein excretion by Bradford assay and erythrocytes and leucocytes by microscopy. Changes were observed when C-4 was compared to the other collection times for all variables investigated. It is possible to conclude that physical exertion induced important changes in the hydration status and glomerular membrane selectivity to macromolecules, modifying the kidney function of the marathoners in C4.